Trade, growth, and global connectivity in the New Zealand context - Chris Nees (New Zealand Institute of Economic Research (NZIER), 2005)
Intended as a contribution to the debate on the sources of New Zealand's export growth, this paper seeks to examine the persistence of New Zealand's trade in commodity products, which have historically made up a large portion of the nation's export receipts. Despite periodic discussion surrounding export strategies such as exhorting exporters to add more value or the need to develop a `knowledge economy', an important part of New Zealand's export returns and New Zealand's income continues to be sourced from bulk commodities. [...] The importance of commodities to New Zealand's export returns is likely to continue as New Zealand's supply side comparative advantage in the production of agricultural products carries on even as the economy diversifies its exports. New Zealand is in a good position to benefit from future liberalisation in world trade (albeit slowly), strong demand for commodities from Asia, and experience gained from doing business in competitive world markets.
Keywords: 330; Weltwirtschaft; Internationaler Wettbewerb; Exportinduziertes Wachstum; Neuseeland